There must be a villain: political threats, narrative thought, and political violence. Issue 1 (1st January 2023) - McLaughlin, Bryan; Dunn, Joshua A.; Velez, John A.; Hunter, Jeffrey
ABSTRACT: This study examined the role political villains play in individuals' political imagination, which can then lead to political violence. When there is a threatening villain, partisans should become more likely to construct elaborate narratives about the political world, which can lead them to believe the violence against the opposition is justified. Study 1 uses a survey to provide evidence that exposure to partisan news sources cultivates the perception that opposing candidate pose a grave danger to America, which leads to more narrative thought. In Study 2, an experiment demonstrates that imagining threatening villains creates more narrative thought, which is then related to support for political violence.